Isu-Isu Global: Polusi, Pemanasan Global, Dan Bencana Alam - Khoirul Huda; Muhammad Arif Halomoan Hsb; Riri Afriani Nasution (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study discusses three interrelated global environmental issues that increasingly threaten the sustainability of human life: natural disasters, pollution, and global warming. These issues have attracted worldwide attention due to their widespread impacts on social, economic, health, and food security aspects. The research employs a literature study method by analyzing various journals, books, and relevant scientific sources to explore the causes, effects, and mitigation efforts. The findings indicate that human activities such as fossil fuel consumption, industrialization, and environmental exploitation are the main factors that exacerbate global warming, increase the risk of natural disasters, and trigger various forms of pollution. The resulting impacts range from ecosystem damage, declining health quality, and increasing disaster intensity to the disruption of community economic stability. Based on these findings, global cooperation, strict environmental policies, and increased public awareness are needed to preserve the Earth sustainably.